The Use of Modified Delphi Technique to Develop the Instrument for Factors of Career Satisfaction among Female Engineers - Subri, Ummu Sakinah; Che Rus, Ridzwan; Mustapha, Ramlee; Hanapi, Zaliza (Journal of Technical Education and Training, 2020)
Women, especially married women are often associated with the dilemma of juggling the balance between career and family and there are statistics showing a declining number of female engineers. This study aims to obtain experts’ conformity on the instrument of Career Satisfaction among female engineers with families. The purpose of such instrument is to determine the factors that influence the level of career satisfaction among female engineers with families using the Modified Delphi technique. The technique is used to gather mutual agreement among experts in developing the items pertaining to Career Satisfaction. The development of instrument involved seven experts with relevant expertise, experience, and knowledge in the field of career and engineering. Findings from the first round (interviewing the experts) report for four main factors in achieving career satisfaction namely mentor, relationship with colleagues, gender equality, and salary. The study also suggests a method to determine the interquartile range via the Modified Delphi technique, which was conducted on the second round until a mutual agreement was achieved. Interquartile range refers to the value obtained from the questionnaire which was answered by the experts in order to determine the mutual values of the construct items and were analysed using the Microsoft Excel. The side factors have the potential to motivate and prompt individuals in achieving high satisfaction and inspiration in their career are Mentor, relationship with colleagues, gender equality, and salary.